Exploring the Impact of Instagram on English Language Skills: Students' Perspectives - Laila, Fitri Nur; Hartono, Rudi; Wahyuni, Sri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The integration of social media platforms into educational practices has become increasingly prevalent, offering innovative ways to enhance language learning. This study explores the role of Instagram in enhancing students' English competence, focusing on its effectiveness in developing vocabulary and listening skills. Employing a qualitative case study approach, the research involved ten senior high school students as participants. Data were collected through semi-structured interviews to gain in-depth insight into their experiences. Findings suggest that Instagram's multimodal features, including captions, videos, and interactive elements, create an engaging and accessible learning environment that encourages language acquisition. While receptive skills showed noticeable improvement, writing and speaking proficiency appeared to require more structured and intentional practice. The study highlights the importance of active engagement in digital learning spaces to maximize Instagram’s potential for holistic language development. This research is particularly useful in the fields of educational technology, language education, and digital pedagogy, offering practical implications for integrating social media platforms into formal language instruction to support comprehensive language skill development. Future research could further explore strategies to maximize Instagram's potential in these areas.